Evaluasi Kinerja Aparatur Pemerintah Desa di Kabupaten Gunungkidul - Sumarni, Sumarni; Ameliya, Ameliya; Kurnianto, Arif (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
The purpose of this research is to determine the performance of village officials in Gunungkidul Regency. Its significance lies in the crucial role of village officials as the implementing element of regional autonomy at the lowest level. Village governments influence the success of government programs in terms of governance. In this study, we used a qualitative descriptive research approach, sampling all sub-districts in Gunungkidul Regency, selecting 1-3 villages (desa or kalurahan) from each sub-district. In this research, we used indicators such as output quality, output quantity, working hours, attendance rate, and collaboration. The analysis used in this research is the fishbone analysis. The results of this study show that the performance of Village Apparatus still requires support for improving the quality of human resources because the average performance of Village Apparatus is still low.